Suitable Investment environment For business sector in Iraq - معلة حالوب كاظم; نظمي داليا عمر (Journal of Economics and Administrative Sciences, 2013)
Investment Bases directly and closely to an environment characterized by political, social and economic stability, and through a range of policies and institutions and economic laws that affect investor confidence and convince him directing investments to country without the other, where inter conditions and circumstances affecting the trends of capital and settle in, and political situation of the country and what is characterized of stability or disorder as well as economic conditions that are affected by what is distinguishes the country from geographic and demographic characteristics are reflected on availability of production elements and country’s infrastructure. Investment is one of important sources of financing development, prompting world countries in different directions to quest for attracting it in different ways, despite the raised political and economic contradictions are still controversial and bitter debate, even in the mother countries of the investing companies. Due to the importance of investing in Filling gap saving – investment. Iraq is seeking to take advantage of world capital money movement for the advancement of the country’s economy .The pursuit of this trend is clearly appeared after 2003 as Law No. (13) Of 2006, as amended. But the concern for investment environment for business remains weak and public sector is the dominant on economic activity. Iraq has occupied, according to Doing Business in 2012 ranked 164 of the total 183 countries where the absence of private information on the work of the private sector, where difficulties when all stages that hinder the practice of business.